A Comparative Exploration of the Pedagogical Quality of Parent-Led Child Care Centers and Regular Child Care in The Netherlands. Issue 1 (2nd January 2019) - Fukkink, Ruben G.; Sluiter, Rosanne M. V.; Gevers Deynoot-Schaub, Mirjam J. J. M.; Helmerhorst, Katrien O. W.
ABSTRACT: Research Findings : This small-scale study features the 1st comparative exploration of the pedagogical quality of parent-led child care and regular child care in The Netherlands. The quality of the interaction skills and the affective relationships between adults and children was evaluated and compared with those of regular child care centers. On average parents in parent-led child care had interactions with adequate to good sensitive responsiveness, respect for autonomy, structuring and limit setting, and verbal communication. Developmental stimulation and fostering positive peer interactions proved to be weaker areas. Parents' perceptions of the affective relationship with children in the group were characterized by a high level of closeness and a low level of dependency and conflict. Parents experienced a greater degree of closeness but also more conflict and in particular greater dependency with their own children than with the other children. A comparison between parent-led centers and regular urban child care centers revealed some small but significant differences in pedagogical quality. Practice or Policy : Parents can play a more active role in both the design and implementation of child care. It seems interesting to pilot new child care formats in which parents and professional staff collaborate more closely.